A numerical and experimental investigation on quasi-static punch shear test behavior of aramid/epoxy composites - EKİCİ, BÜLENT (SAGE PUBLICATIONS LTD, 2020)
In this study, quasi-static punch shear behavior of aramid epoxy composites was investigated both numerically and experimentally. Firstly, material model parameters used in numerical simulations were obtained by various mechanical tests such as tensile, compression, and in-plane shear tests. Different damage mechanisms that were observed during each test were the focus of interest. Then quasi-static punch shear test was performed and verified with numerical simulations. After the verification of material model, punch tests, which have different boundary conditions, were run numerically, and the effect of thickness and span-to-punch ratio (SPR) were determined for aramid/epoxy composites. It is concluded that failure mechanisms of composite samples were related to SPR. When SPR increases, the failure mode was shifted from shear-dominated failure to bending-dominated failure behavior. Additionally, punch shear strength value at minimum SPR (1.1) was eight times bigger than the value at maximum one (8).
Keywords: Polymer matrix composites; damage mechanics; quasi-static punch shear test; numerical modelling; LOW-VELOCITY IMPACT; PROGRESSIVE DAMAGE; PENETRATION MODEL; BALLISTIC IMPACT; PERFORATION; PLATES; PANELS